2006
DOI: 10.1063/1.2159083
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the amplified spontaneous emission from thiophene/phenylene co-oligomer single crystals: Towards co-oligomer lasers

Abstract: Photoluminescence ͑PL͒ and optical gain measurements have been performed for single crystals of thiophene/phenylene co-oligomer at room and low temperatures. Broad PL bands are transformed to be an ensemble of several spectrally narrower vibronic peaks with decreasing temperature. Very sharp lines as narrow as ϳ3 meV are observed at 10 K under weak excitation. Intensities of sharp emission lines superlinearly increased at 10 K under intense excitation, showing the amplified spontaneous emission ͑ASE͒. The ASE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
(31 reference statements)
2
42
0
Order By: Relevance
“…This value is one of the lowest reported in the literature for molecular materials, without energy-transfer processes being involved. Moreover, it is comparable to thresholds of typical semiconducting polymers emitting in the blue region of the optical spectrum (see comparison in Table 1) [17,[27][28][29][30][31]. Note that thresholds in Table 1 are given in power density units (kW=cm 2 ), which are the most convenient to compare the performance of different materials [15].…”
Section: Introductionmentioning
confidence: 94%
“…This value is one of the lowest reported in the literature for molecular materials, without energy-transfer processes being involved. Moreover, it is comparable to thresholds of typical semiconducting polymers emitting in the blue region of the optical spectrum (see comparison in Table 1) [17,[27][28][29][30][31]. Note that thresholds in Table 1 are given in power density units (kW=cm 2 ), which are the most convenient to compare the performance of different materials [15].…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, reabsorption could not occur during irradiation above the amplified spontaneous emission (ASE) threshold because reabsorption hardly occurs during population inversion. Bando et al reported the emission behavior of a BP1T single crystal under dye laser excitation (400 nm, 30 ns) [16]. They found that the intensity of the narrow peak at 465 nm was half that of the peak at 495 nm.…”
Section: Resultsmentioning
confidence: 98%
“…These phenyl-thiophene co-oligomers have attracted attention due to their potential as active components in OLEDs, organic diode lasers, and p-type semiconductors in OFETs [80,[234][235][236][237][238][239][240][241][242][243]. Noteworthy features are electroluminescence [237], and emission gain narrowing like spectrally narrowed emission (SNE) [244][245][246], and amplified spontaneous emission (ASE) caused by self-waveguide effects [247][248][249], and even mirrorless lasing [250,251].…”
Section: Discussionmentioning
confidence: 99%